Genetic variation in growth and yield components of juvenile balsam poplar (Populus balsamifera L.) growing in northwestern Ontario / by Frank Schnekenburger - Schnekenburger, Frank (My University, 1988)
A nursery and greenhouse study of balsam poplar (Populus balsamifera L.) were carried out in Thunder Bay, Ontario, to study the extent and nature of variation in growth and its relation to the following yield components: phenology, assimilation rate, leaf morphology, and assimilate distribution. The studies involved clones of four sources of balsam poplar selected along an approximate latitudinal gradient: N. Wisconsin (45-46®N), Thunder Bay (48-49®N), Pickle Lake (51-52®N), and Severn River (53-54®N). As part of the greenhouse study, the effects of a reduction in the daily period of photosynthate production were studied. For this purpose, plants were grown under either a normal or reduced photosynthetic period of approximately 16 or 8 hours per day, respectively. The reduced photosynthetic period was achieved W covering plants with opaque shade cloth from 4:00 p.m. of one day until 8:00 a.m. of the next day. Low-level incandescent lighting provided cua 18-hour photoperiod that prevented height growth cessation under both photos3mthetic periods. The nursery study demonstrated significant variation among clones of the Thunder Bay and Pickle Lake sources, in terms of date of bud break and growth cessation, initial plant height, and total shoot elongation. Date of growth cessation differed significantly between sources, occurring eight days earlier for the Pickle Lake source than for the Thunder Bay source; source differences in date of bud breads: were not significant. Total shoot elongation was moderately correlated with date of growth cessation, but not with date of bud break. The greenhouse study entailed assessment of clones from all four sources. Clonal variation was significant in terms of leaf, stem, and root dry weight; leaf area and number; shoot length; and root number. Relative growth rate (RGR) differed significantly among sources; clonal variation in RGR and in relative leaf weight growth rate (RLwGR) and relative leaf area growth rate (RLaGR) was significant for some sources, but not others. Differences in RGR were closely linked to differences in unit leaf rate, but not to leaf growth characteristics. Plants under the reduced photosynthetic period produced less dry weight and leaf area, fewer leaves, and less shoot growth than those lander the normal photosynthetic period. Relative growth rate, unit leaf rate, and the allometric constant relating the relative rate of shoot growth to that of root growth were also lower under the reduced photosynthetic period. Leaf area ratio was greater under the reduced photosynthetic period, largely due to greater specific leaf area. Marked changes in clonal rankings based on relative growth rates suggest that differences exist among the clones studied in their response to the reduced photosynthetic period. In general, the reduced photosynthetic period affected the southern sources to a lesser degree than the northern sources.
Keywords: Poplar Ontario, Northwestern; Poplar; Forest genetics